The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40841-020-00179-9
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of New Zealand’s Exclusive Approach to Intercultural Education

Abstract: This article examines the intercultural initiatives, programmes and strategy documents in New Zealand education to answer the following two questions: What intercultural policies and strategy documents are offered to New Zealand schools and teachers to accommodate their diverse communities? Which communities do they include and/or exclude? It explores and discusses paradigms, policies and curriculum developments that have been developed to address the growing levels of diversity in New Zealand’s schools and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…In other words, rather than focusing on people who suffer discrimination and abuse, perpetrators of discrimination need lessons in intercultural education. The need for inclusive intercultural education is an argument which has been made by scholars too (Salahshour 2020).…”
Section: Information Needs Of the Communitymentioning
confidence: 99%
“…In other words, rather than focusing on people who suffer discrimination and abuse, perpetrators of discrimination need lessons in intercultural education. The need for inclusive intercultural education is an argument which has been made by scholars too (Salahshour 2020).…”
Section: Information Needs Of the Communitymentioning
confidence: 99%
“…Against the backdrop of international literature and that with regard for Māori learners, a smaller body of research has explored effective teaching in superdiverse classrooms and early childhood education [ECE] centres in New Zealand (e.g. Chan, 2020;Cardno et al, 2018;Salahshour, 2020). For example, Chan's (2020) exploration of multicultural ECE centres found that the intentional inclusion of non-mainstream-centric resources (such as stories, songs, dance) into everyday practices normalised and valued diverse ways of life.…”
Section: Culturally Sustaining Pedagogy In Aotearoa New Zealandmentioning
confidence: 99%
“…As a result, they found that approaches to minority ethnic groups were uneven. Our study intended to contribute to this small base of research on highly multi-cultural learning environments in New Zealand (Salahshour, 2020).…”
Section: Culturally Sustaining Pedagogy In Aotearoa New Zealandmentioning
confidence: 99%
See 1 more Smart Citation
“…An overarching language policy would help navigate and build awareness of Aotearoa's complex linguistic diversity ultimately supporting social cohesion within this country -an overarching goal for Aotearoa New Zealand suggested in the human rights commission report investigating the Christchurch Mosque shootings (Royal Commission, 2021;Salahshour, 2021).…”
Section: 'Ethnic Enhancement' To Bolster Current Programmes and Initiativesmentioning
confidence: 99%